Revised stratigraphy of the Cookson Group in eastern Maine and southwestern New Brunswick: an alternate view - Ludman, Allan (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
Fossil evidence reported by Fyffe and Riva (1990) requires inversion of the stratigraphic succession originally proposed for the St. Croix Terrane (Ludman, 1987). Other suggested revisions, however, are not in accord with structural and sedimentologic data in eastern Maine. Comparison of structural histories indicates that the Pocomoonshine Lake and Digdeguash formations are more appropriately part of the Frederic ton Belt than of the St Croix Terrane as suggested by fyffe and Riva(1990). An alternate view of the stratigraphic and tectonic relationships between the St Croix Terrane and Fredericton Belt includes the following changes: the Pocomoonshine Lake Formation, originally assigned to the St Croix Terrane, is now considered to be the oldest unit of the Fredericton Belt, lying conformably below the Digdeguash Formation; a late Acadian thrust fault is thought to have transported the St Croix Terrane westward over the Fredericton Belt; subsequent high-angle dip-slip and strike-slip faulting have obscured original relationships—these faults now form the boundary between the two terranes in southeastern Maine.